2007
DOI: 10.1111/j.1365-2788.2006.00902.x
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen‐year follow‐up of 92 hospitalized adults with Down’s syndrome: incidence of cognitive decline, its relationship to age and neuropathology

Abstract: Clinical dementia associated with measurable cognitive and functional decline is frequent in people with DS after middle age, and can be readily diagnosed among less severely intellectually disabled persons using measures of cognitive function such as the PCFT and behavioural scales such as the ABS. In the more profoundly disabled people, the diagnosis of dementia is facilitated by the use of behavioural and neurological criteria. In this study, the largest prospective DS series including neuropathology on dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
113
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 44 publications
(48 reference statements)
4
113
0
4
Order By: Relevance
“…6,15,33,34 As previously stated, this disorder is associated with substantial comorbidity and mortality, and frequently overshadows the diagnosis of the other disorders of aging. 34 Differential diagnosis requires the exclusion of other causes of cognitive decline such as medical conditions, medication effects, psychiatric disorders, changes in environment/bereavement and abuse 9,14,35 It is also essential to correctly differentiate age-related cognitive decline from early dementia, 9 since cognitive abilities in most people with DS are below the average level even before they develop dementia, 32 and the domains of communication and socialization are markedly affected by age. 36 Thus, a baseline assessment of functioning must be established for future reference and comparison.…”
mentioning
confidence: 99%
“…6,15,33,34 As previously stated, this disorder is associated with substantial comorbidity and mortality, and frequently overshadows the diagnosis of the other disorders of aging. 34 Differential diagnosis requires the exclusion of other causes of cognitive decline such as medical conditions, medication effects, psychiatric disorders, changes in environment/bereavement and abuse 9,14,35 It is also essential to correctly differentiate age-related cognitive decline from early dementia, 9 since cognitive abilities in most people with DS are below the average level even before they develop dementia, 32 and the domains of communication and socialization are markedly affected by age. 36 Thus, a baseline assessment of functioning must be established for future reference and comparison.…”
mentioning
confidence: 99%
“…Postmortem studies have shown that, after reaching 40 years of age, virtually all individuals with DS show neuropathological signs of AD, including senile plaques and neurofibrillary tangles [9,10]. Because of the pathological similarity of AD among individuals with DS in the fourth decade of life, DS in such individuals can be considered a model for the development of AD, even if the degree of neuropathological severity is not directly related to the clinical characteristics presented [11]. Neuroimaging studies have identified typical brain atrophy in patients with DS and AD [12], as well as indicators of dementia correlated with structural and functional findings in individuals with DS without clinical signs of AD but at the age of risk for its development [13].…”
Section: Introductionmentioning
confidence: 99%
“…The amyloid precursor protein (APP) gene is present on chromosome 21, and its triplication has been thought to be largely responsible for the early age of onset The objective of this study was to examine associations between the age of onset of dementia in DS and the tau H1/H2 haplotype. We have also analysed the APOE genotype as it has been involved in the association between the extended tau haplotype and AD, and the attt [5][6][7][8] genotype which affects the age of onset of dementia in DS.…”
Section: Introductionmentioning
confidence: 99%
“…This pathology consists not only of amyloid plaques, but also of neurofibrillary tangles (NFTs) [3] with hyperphosphorylated tau in the form of paired helical filaments. The NFTs develop at a later age in DS than amyloid plaques [4] , but importantly are correlated with the presence of dementia [5,6] .Genetic factors may be responsible for the large age range over which dementia develops in DS. For example, a tetranucleotide repeat in intron 7 of APP (attt 5-8 ) has been associated with an earlier age of onset of dementia [7] .…”
mentioning
confidence: 99%
See 1 more Smart Citation